Climate change-related warming-induced shifts in leaf chemical traits favor nutrition of the specialist herbivore Battus polydamas archidamas - González-Teuber, Marcia; Palma-Onetto, Valeria; Aguirre, Carolina; Ibáñez, Alfredo J.; Mithöfer, Axel (Frontiers in Ecology and Evolution, 2023)
One of the major impacts of climate change is increasing global temperatures. Because warming is expected to affect plant morphological and chemical traits, it may therefore also influence plant interactions with other trophic levels, including herbivores. Here, we simulated a climate warming scenario of +2.7° C in the field using open‐top chambers and assessed the effects of warming on plant performance (growth, leaf area and chlorophyll), leaf nutrients (nitrogen and carbon), and primary (amino acids and carbohydrates) and secondary (toxic aristolochic acids) metabolites in the plant Aristolochia chilensis. We performed untargeted metabolomics analyses for estimating general changes in foliar metabolites between ambient control and warming-treated plants. Bioassays were additionally conducted to evaluate how changes in host plant chemistry affected growth and nutritional parameters in first-instar larvae of the specialist lepidopteran herbivore Battus polydamas archidamas. We found that warming did not significantly affect plant performance, but did result in significant changes in leaf nutrients, and primary and secondary metabolites, although in opposite directions. While primary metabolites (specifically, nitrogen-containing compounds) decreased in response to treatment, aristolochic acids increased. Untargeted metabolomics analyses showed that, of a total of 824 features, 50 were significantly different between ambient control and warming-treated plants; some of these were identified by MS/MS spectra as amino acids. Larvae feeding on warming-treated plants, showed significantly enhanced growth, food conversion efficiency, and lipid concentration. Our study contributes to current understanding of climate change impacts on trophic interactions, showing that projected temperature increases lead to changes in the resistance phenotype of the host plant, favoring nutrition and growth of a unique specialist herbivore.